Strikes and Austerity in Portugal: Perspectives, Expression and Recomposition - Costa, Hermes Augusto (2015)
Against the background of worsening employment conditions and increasing imbalances in labour relations, this text discusses the importance of the strike phenomenon in the context of austerity. The first section presents some sociological perspectives on strikes, specifically those relating to notions of democracy and socio-legal regulation, ideology/ies and tensions between collective and individual action, issues of scale and controversies, and timing and outcomes. The second part adopts a quantitative approach and seeks to determine whether the theoretical potential for conflict can be verified in concrete terms. Finally, it discusses the experience of a strike by workers in a specific precarious sector (employees at the “Saúde 24” medical helpline), which provides scope for an assessment of the challenges facing trade union activity and reflections on new ways of organising social conflict.